2012
DOI: 10.1038/ncomms1670
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic neurogenesis in the adult hippocampus does not involve amplification of Ascl1high intermediate progenitors

Abstract: neural stem/progenitor cells generate neurons in the adult hippocampus. neural stem cells produce transient intermediate progenitors (type-2 cells), which generate neuroblasts (type-3 cells) that exit the cell cycle, and differentiate into neurons. The precise dynamics of neuron production from the neural stem cells remains controversial. Here we lineage trace notchdependent neural stem cells in the dentate gyrus and show that over 7-21 days, the progeny of the neural stem cells progress through an Ascl1 high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 59 publications
6
84
0
Order By: Relevance
“…NSCs in the DG of the adult mouse are Notch-dependent and express the Notch target Hes5 (Lugert et al, 2010(Lugert et al, , 2012. Drosha is expressed by most cells in the DG including GFAP + and Hes5 + radial NSCs ( Figure S1A and S1B).…”
Section: Drosha Deletion From Adult Dg Nscs Impairs Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…NSCs in the DG of the adult mouse are Notch-dependent and express the Notch target Hes5 (Lugert et al, 2010(Lugert et al, , 2012. Drosha is expressed by most cells in the DG including GFAP + and Hes5 + radial NSCs ( Figure S1A and S1B).…”
Section: Drosha Deletion From Adult Dg Nscs Impairs Neurogenesismentioning
confidence: 99%
“…0.001 (**) 0.006 (**) 0.005 (**) 0.003 (**) (Chong et al, 2008;Harfe et al, 2005;Lugert et al, 2012;Tchorz et al, 2012). All mice were maintained on a C57BL6 background and were 8-10 weeks old at the onset of the experiments.…”
Section: Table S4 Related To Figure 4 and Figure S4mentioning
confidence: 99%
See 1 more Smart Citation
“…Using a Notch reporter line, in which cells with ongoing Notch/RBPJK are GFP labeled (Hes5::GFP), the authors found that NSCs of SGZ with Notch/RBPJK signaling are the most multipotent of the total progenitors. In basal conditions these NSCs are, for the large part quiescent, but can rapidly switch into a neurogenic mode in response to maximal activity or exercise (Lugert et al, 2010(Lugert et al, , 2012. This important study indicates that the regenerative potential of neuronal progenitors is responsive to increased synchronized activity.…”
Section: Notch In Postnatal Neurogenesismentioning
confidence: 92%
“…The production of new neurons in the adult hippocampus is a tightly orchestrated, multi-step process involving the maintenance, activation and proliferation of stem cells, differentiation and migration of intermediate progenitors, and maturation and integration of newborn neurons [25][26][27]. Under basal conditions, neural stem cells can either be in a resting, quiescent state, or they can be actively dividing [23,28,29].…”
Section: Adult Hippocampal Neurogenesismentioning
confidence: 99%